Empowering Women through Education, Ecology, and Economy: A Psychological Empowerment Approach by Gawah Bonga Foundation - Kurniarais, Salsya Yuniar; Citra Kumala Putri (Prospect Publishing, 2025)
Child marriage remains a culturally legitimized practice among the Sasak people through the merariq selarian tradition. This tradition often places women in subordinate roles, depriving them of fundamental rights to education and economic opportunities. The Gawah Bonga Foundation emerges as a local initiative promoting social transformation through a psychological empowerment approach. This study aims to explore how women’s empowerment is fostered through educational, ecological, and economic programs. Using a descriptive qualitative method, this research examines the experiences of women involved in GBF programs in Dusun Bonga. The findings reveal improvements across the three dimensions of psychological empowerment: intrapersonal, interactional, and behavioral. Women demonstrate increased confidence, critical thinking skills, and active participation in their communities. GBF also utilizes religious and cultural approaches to cultivate critical awareness and strengthen women's agency. These results affirm that effective women’s empowerment must be rooted in local contexts and holistic participatory strategies.